1966
DOI: 10.1111/j.1469-7998.1966.tb03001.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of Malpighian tubules and associated structures inPhilosamia ricini (Lepidoptera, Saturnidae)

Abstract: The morphology of the Malpighian tubules and associated structures in the larva and adult of Philosamia ricini Hutt has been described and an account has been given of the embryonic development of, and post‐embryonic changes in, these structures. The proctodaeum is believed to be entirelyectodermal and so are the Malpighian tubules and the vesicles derived from it. The development of cryptonephric condition and its disappearance duringmetamorphosis have been worked out in detail. The pattern of growth and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1969
1969
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…La estructura celular de los túbulos de Malpighi ha sido ampliamente estudiada en insectos tanto en larvas como en adultos. En algunos Lepidoptera los túbulos crecen por elongación de las células y poliploidización durante el desarrollo larval, mientras que durante la metamorfosis estos permanecen intactos o sufren histólisis (Srivastava y Khare 1966;Ryerse 1979;Rigoni et al 2004). Durante el desarrollo larval del "minador de los cítricos" los extremos distales de los túbulos de Malpighi desembocan en el recto, formando el sistema criptonefridial (Vaca y Michel 2016).…”
Section: Discussionunclassified
“…La estructura celular de los túbulos de Malpighi ha sido ampliamente estudiada en insectos tanto en larvas como en adultos. En algunos Lepidoptera los túbulos crecen por elongación de las células y poliploidización durante el desarrollo larval, mientras que durante la metamorfosis estos permanecen intactos o sufren histólisis (Srivastava y Khare 1966;Ryerse 1979;Rigoni et al 2004). Durante el desarrollo larval del "minador de los cítricos" los extremos distales de los túbulos de Malpighi desembocan en el recto, formando el sistema criptonefridial (Vaca y Michel 2016).…”
Section: Discussionunclassified
“…In some insects it can be clearly shown that the Malpighian tubules are budded off from the proctodaeal invagination of the embryo before the mesenteron has formed (e.g. Srivastava & Khare, 1966): hence the traditional view is that the tubules are ectodermal and by implication any tissue occurring posterior to the point of attachment of the tubules would be ectodermal also. However, a substantial body of opinion now supports the contention that parts of the Malpighian tubule are endodermal, owing to their histological and ultrastructural resemblance to the midgut (Butt, 1949;Savage, 1956;1962;Wall, Oschman & Schmidt, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…In these insects the larval Malpighian tubes persist in the adult with little redifferentiation, e.g. in Hyponomeuta padella L. (Hufnagel, 1918), Bombyx mori L. (Ito, 1921), Aglais (Vanessa) (Henson, 1939), Philosamia ricini (Srivastava & Khare, 1966).…”
Section: (4) Comparison Of the Changes During Metamorphosis In The Mamentioning
confidence: 99%